Kedudukan dan Hak-Hak Anak Dalam Perspektif Al-Qur'an (Sebuah Kajian dengan Metode Tafsir Tematik) - Mustaqim, Abdul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
The Qur'an is very appreciative toward children's issues. This can be seen from the number of Qur'anic verses addressing the affairs of children, especially their rights. In the real life, however, parents and governments have not paid adequate attention to the rights of children. This article aims to elaborate the rights of children as they are invoked in the Qur'an. By employing a mudlu'i method of interpreting the Qur'an, it can be concluded that the Qur'an has conceptualized children as folows: 1) they are God's gift whose presence should be gratified; 2) children are a trust (amanat) from Â God whose rights should be guaranteed; and 3) children are as a test (fitnah) for parents' patience. In order to implement the idea of children as precious gifts who generate happiness and proud (qurrata a'yun), the rights of children should be respected. Some of their basic rights are: 1) to live a goodÂ life; 2) to receiveÂ breast feeding for up to two years; 3) to adhere to religion; 4) to have education free of violence; 5) to express their opinions.